PERAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP INOVASI MAHASISWA YANG DIMEDIASI PENGENALAN PELUANG WIRAUSAHA - Dita Maharani Suwardi; Amir Machmud; Iswanti Iswanti (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThis research aims to find out and analyze the role of mediation from the introduction of entrepreneurial opportunities to entrepreneurial education and innovation. This research is  quantitative research with survey method. The research population is students majoring in economic education siliwangi University with the number of respondents taken amounted to 183 respondents using the formula Slovin and purposive sampling techniques. The data has been collected and processed using track analysis techniques. The results of the analysis prove that the variables of entrepreneurial education and entrepreneurial opportunities recognition have a significant influence on innovation, as well as the role of entrepreneurial opportunities recognition capable of mediating entrepreneurial education to innovation. This means that entrepreneurial education variables influence innovation mediated by entrepreneurial opportunities recognition. The results of this study provide implications that with entrepreneurial opportunities recognition can help students know their entrepreneurial orientation by being encouraged by the entrepreneurial education obtained in the study so that students can foster innovation in students.Keywords: Entrepreneurship Education, Innovation, Entrepreneurial Opportunities Recognition.